Analisis Lintas Sifat Morfo-Agronomis dan Fisiologis Jagung (Zea mays L.) - Annisa Malik; Farit Mochamad Afendi; Akbar Rizki; . Sutoro (Xplore: Journal of Statistics, 2018)
Corn (Zea mays L.) is the third most important food commodity after wheat and rice based on the world's staple food, and ranks second after rice based on staple food in Indonesia. High yielding varieties of corn are highly needed to meet food, feed and industrial needs. These varieties can be obtained through plant breeding programs by utilizing the source of genes capable of producing good plant character. Gene sources can be obtained from germplasm or local varieties that exist. Character of plants that can support the productivity of plants can be used as an indicator of the selection process in corn plant breeding. This can be done through characterization of morpho-agronomic and physiological properties of each corn variety, then determine the characters that support the productivity of corn plants directly or indirectly. The direct and indirect effect of a plant's character on crop productivity is identified through path analysis. The results showed that the effective selection criteria for increasing corn’s seed weight directly was the leaf area. While the effective selection criteria for increasing the weight of biomass directly is the age of female flowers out. While the effective selection criteria for increasing corn’s seed weight and biomass indirectly is the plant height through the filling rate of the seeds.